Foreign background and older age of children were associated with infection in Swedish tuberculosis contacts. (8th February 2020) - Bennet, Rutger; Nejat, Sahar; Eriksson, Margareta
Abstract: Aim: We present our results using interferon‐gamma release assays in any child <18 years or tuberculin skin tests in Bacille Calmette‐Guérin unvaccinated children for tuberculosis contact investigation in Stockholm, Sweden. Methods: During 2000—2019, we investigated 892 children with a median age of seven years. We explored associations between TB infection and characteristics such as closeness to contact, age, sex, BCG status and foreign origin. Results: The overall rates were for TB infection 10.2% (n = 91) and for TB disease 1.1% (n = 10). In addition to infectiousness of index case and closeness of contact, foreign background, male sex and increasing age were independently associated with infection. In foreign‐born children, the rates of tuberculosis infection and disease were 18.7% and 3.9%, respectively. In 18/46 (39%) infected foreign‐born children, a baseline negative tuberculosis test supported a diagnosis of recent infection. Conclusion: Foreign background, older age and male sex were associated with infection. In a significant proportion of infected children, a previous negative test made recent infection likely.